Analisis Kinerja Karyawan PT. Batam Bintan Telekomunikasi Dalam Kaitannya Dengan Motivasi, Disiplin, dan Stres Kerja - Juniastito, Raynaldi; Ngaliman, Ngaliman; Yanti, Sri (Zona Manajerial: Program Studi Manajemen (S1), 2023)
PT Batam Bintan Telekomunikasi (BBT) has its own uniqueness as a corporation. This company only provides communication services outside PT Telkom for industrial areas in Batam and Bintan which are being developed by the Salim Group. The purpose of this research is to analyze the performance of employees PT BBT, in relation to the influence of motivation, discipline and work stress. The study was conducted on 40 employees of the Company through data collection processed with SPSS version 24. The results of the analysis prove that motivation (X1) shows a positive influence on employee performance. Likewise regarding the influence of discipline (X2) on performance and work stress (X3) on employee performance.